2016
DOI: 10.1038/srep20864
|View full text |Cite|
|
Sign up to set email alerts
|

Selective inhibition of EZH2 by ZLD1039 blocks H3K27methylation and leads to potent anti-tumor activity in breast cancer

Abstract: Enhancer of zeste homolog 2 (EZH2) is a candidate oncogenic driver due to its prevalent overexpression and aberrant repression of tumor suppressor genes in diverse cancers. Therefore, blocking EZH2 enzyme activity may present a valid therapeutic strategy for the treatment of cancers with EZH2 overexpression including breast cancers. Here, we described ZLD1039 a potent, highly selective, and orally bioavailable small molecule inhibitor of EZH2, which inhibited breast tumor growth and metastasis. ZLD1039 conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…With more and more research available, the epigenetic molecule EZH2 is regarded as a transcriptional repressor associated with many cancer types [14,15,16,17]. Our previous study demonstrated that compared to normal tissues, colorectal cancer tissues expressed higher levels of EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…With more and more research available, the epigenetic molecule EZH2 is regarded as a transcriptional repressor associated with many cancer types [14,15,16,17]. Our previous study demonstrated that compared to normal tissues, colorectal cancer tissues expressed higher levels of EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…46 Again, on the basis of 6 , ZLD1039 ( 10 ), which is 12-fold selective for EZH2 over EZH1, has been discovered. 47,48 Most recently, compound 11 , a potent EZH2 inhibitor, was cocrystallized with the active Ac /human PRC2 complex. 14 …”
Section: Introductionmentioning
confidence: 99%
“…EZH2 overexpression has been identified in NPC, non-small cell lung cancer, chronic lymphocytic leukemia and breast cancer (15)(16)(17). Collectively, these studies suggest that EZH2 is a novel target oncogene and pharmacological inhibition of EZH2 may be therapeutic for certain types of cancer.…”
Section: Discussionmentioning
confidence: 93%